A Portable Sensor System with Ultramicro Electrode Chip for the Detection of Heavy-Metal Ions in Water - Yuekun Wang; Yuhao Xu; Jinhua Jiang; Yang Li; Jianhua Tong; Chao Bian (Micromachines, 2021)
In this study, an ultramicro interdigital electrode array chip (UIEA) was designed and fabricated by using Micro-Electro-Mechanical systems (MEMS) technology, and a portable detection system, using the chip for determination of heavy-metal ions in water, was developed. The working electrode of the UIEA was modified with gold nanoparticles by electrodeposition. The detection sensitivity of the UIEA chip for copper ions was 0.0138 μA·L·μg−1, with the linear range of 0–400 μg/L and the detection limit of 18.89 μg/L (3σ), which was better than that of the compared columnar glassy carbon electrode. The results of the interference experiment verified that the UIEA chip has a certain anti-interference ability against common heavy-metal ions in water, such as Pb2+, Zn2+, and Mg2+ ions. The standard addition method was used to investigate the performance of the developed s ystem for copper ion determination in real water. The recovery range from 87.5% to 94.7% was achieved.